A shift in time: music and temporality in 1913 Paris - Davies, EA (2020)
Temporality is an integral—and often overlooked—aspect of music. This thesis seeks to understand the relationship between music and time. Rapid social, cultural and technological change affected the perception and experience of temporality in fin de siècle Paris. The year 1913 offers a fascinating case study for understanding the plethora of cultural and musical reactions to these changes. To that end, this thesis draws on a range of primary and secondary sources such as journalistic texts, letters, notes, philosophical texts, visual arts, cinematic and musical sources, and makes use of interdisciplinary methodology, drawing upon historical musicology, socio-cultural history and philosophies of time.